Hubungan Usia Kehamilan, Riwayat Abortus Dan Paritas Terhadap Kejadian Preeklampsia Berat Di RSUD Abdoel Wahab Sjahranie Tahun 2022 - Sitohang, Yeni Maria Rosalina; Ismansyah, Ismansyah; Siregar, Nursyahid (Jurnal Skala Kesehatan, 2023)
Introduction : In 2021, Abdoel Wahab Sjahranie Hospital recorded a total of 55 pregnant mothers suffering from severe preeclampsia. Preeclampsia can be treated by controlling the risk factors it carries. This study examines the relationship between gestational age, prior miscarriage record, and parity which incited severe preeclampsia cases in Abdul Wahab Sjahranie Hospital. Method : This research is an observational analytical study with case control design. A total sample of 110 respondents was taken from medical record data in 2021. The PEB group sample was taken using total sampling and the control group was taken by quota sampling. The bi-variate analysis was conducted with chi-square test. Results : From the test conducted, gestational age has Pvalue of 0.008 and odd ratio of 0.244 . In addition, prior miscarriage has Pvalue of 0.041 and odd ratio of 2.628. Lastly, parity has Pvalue of 0.038. Discussion : Growing and aging placenta with gestational age more than 34 weeks will limit intervillous perfusion which causes secondary syncytiotrophoblast stress and the release of placental factors into the maternal bloodstream, maternal alloimmune response to fetal trophoblasts resulting in miscarriage, and primiparous parity due to first-time exposure to chorionic villi, whereas the case in grandemultipara is associated with a decrease in the function of reproductive system and nutritional fulfillment which lead to preeclampsia. Conclusions : Early detection of preeclampsia requires a more complete diagnostic procedure and it is associated with maternal and neonatal morbidity. Keywords: Gestational Age, Prior Miscarriage, Parity, Preeclampsia